« Posture Zoo-futuriste » et réanimalisation de l’humain - Lestel, Dominique (Anthropologica, 2020)
This article brings to the fore an emerging cultural trend in terms of relations to animals that goes beyond contemporary animalist movements and is referred to as “Zoo-futurism.” The objective is not merely to cohabit with animals, but to go and inhabit animals while allowing some of them to come and inhabit oneself. The article identifies the six stages through which one species can transit to another, and then shows that, in any case, it is impossible to satisfactorily define a notion as fundamental as that of species. The article ends by attempting to determine the meaning of this contemporary movement of reanimalization of humankind.